The effects of acid rain on stone monuments - Arslan, M; Kaygili, H; Arslan, C; Çil, E; Begdili, H (Parlar Scientific Publications (P S P), 2003)
In this study, the effect of acid rain on historical monument samples in the ruins of Ahlat (Bitlis, Turkey) were investigated. The effects of pH, contact time and temperature on the solubility of Ca, Mg, Al, K and Fe of monuments were examined. Fe concentrations were below the detection limits of AAS analysis. The concentrations of ions in the run-off solutions are generally the highest at low pH values. Calcium has the maximum solubility at pH 2 and 25 degreesC, 10. 1 mg L-1 per 1 h. Increasing acidity and temperature increase erosion effects of the monuments.
Keywords: acid rain; monuments; erosion